ENHANCING THE MSME'S SUSTAINABILITY OF WARUNG MAKMI THROUGH STRATEGIC BRANDING, PRODUCT INNOVATION, AND DIGITAL PROMOTION - Kawuryan, Renita; Piar, Christie Stephanie; S., Fauziah Lily Anggraeni; Sampeallo, Yulius Gessong (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
This community development activity focuses on enhancing the sustainability of a small food business, Warung Mak Mi, through strategic branding, product innovation, and digital promotion. Recognizing the critical role these strategies play in the success of Micro, Small, and Medium Enterprises (MSMEs). The key steps include enhancing the brand identity, fostering innovative product offerings, and optimizing promotional efforts through social media platforms.The findings suggest that by implementing enhanced branding techniques, innovative product offerings, and optimized social media promotion, Warung Mak Mi can significantly improve its product quality and sales performance. The study concludes with actionable recommendations for leveraging the knowledge gained from the training sessions to achieve sustainable growth and long-term success. This activity reaffirms the importance of continuous learning and adaptation for MSMEs to thrive in a competitive market, positioning Warung Mak Mi for future success.